Current Knowledge on Psychic Stress in Surgical Procedures - Márcia Rodrigues Daian; Andy Petroianu; Luiz Ronaldo Alberti (Open Journal of Biological Sciences - Peertechz Publications, 2016)
The incidence of stress among individuals submitted to major surgery is relevant. Although it has been noted that some patients go through the perioperative period without presenting stress, surgical patients have a high probability of presenting one of the four phases of stress. Recognizing the stress phase that affects the patient permits the medical team to act in a more appropriate manner and to propose interventions that will prevent worsening of the disease and an unsuccessful outcome of surgery. The main objective of this paper was to present a review of the most important aspects regarding psychic stress in patients undergoing major operations under general anesthesia.